Stray [videorecording (DVD)] (Magnolia Home Entertainment, 2021)
Through the eyes of three stray dogs wandering the streets of Istanbul, the film explores what it means to live without status or security. As they search for food and shelter, Zeytin, Nazar and Kartal embark on inconspicuous journeys through Turkish society that allow viewers an unvarnished portrait of human life through the unfamiliar gaze of dogs.